Can the Affective Commitment and Job Satisfaction Mediate The Impact of Job Embeddedness on Turnover Intention? - Nadilah Rahma Sari; Widiya Dewi Anjaningrum (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this survey to examine and analyze the relationship of research and analysis, affective commitment, job satisfaction, and employee turnover intention. This study uses a survey method with data collection. Samples from 30 employees of CV Cipta Utama Mandiri were taken using purposive sampling and analyze by SmartPLS-3.3.5 software. The results of this study prove that high turnover intention is significantly influenced by affective commitment. This influence is negative, because employees who have strong emotional ties to the company feel they are part of the company which makes the employee reluctant to want to resign from the company. The findings also show that there is no significant negative effect of job embeddedness and job satisfaction on turnover intention. The mediating role of job satisfaction on the effect of job embeddedness on turnover intention is also not proven. However, strong affective commitment can convey the impact of job embeddedness on turnover intention.